Optimizing the Facility Location Design of Organ Transplant Centers in Turkey - ZENKHRI, AMINE (İstanbul Kültür Üniversitesi, 2023)
Organ transplantation is one of the most vital components of healthcare systems and is a very important surgical treatment for many diseases that can be fatal if not applied. Despite all the advances and sophisticated technologies in operational and transportation methods in the field of health services in the last two decades, the number of patients who lost their lives due to organ failure is increasing in Turkey as well as in the rest of the world. Due to the increasing need for organs, matching the donated organs with the most suitable recipient patients in an efficient and fair manner is one of the most important processes. Therefore, the need to optimize and monitor the organ procurement and distribution process has inevitably increased. The main purpose of this study is to develop a mathematical model that will determine the number of regional coordination centers in Turkey, where a hierarchical system is used for organ transplantation. In addressing this problem, the effects of cluster structures on potential organ pairings will be explored. The mathematical model is designed to include key constraints such as duration and different types of organs. The optimization model tries to minimize the total travel time between the transplant centers and the donor hospitals assigned to the same regional center (RC). The proposed MILP model is solved using a commercial solver, i.e. GAMS.
Türkiye'deki Organ Nakli Merkezlerinin Tesis Yer Tasarımının Optimizasyonu
▪ Yüksek lisans tezi.
Keywords: Organ Transplant; Facility Location; Mixed Integer Linear Programing (MILP); Ischemia Time